Teaching Style and Student Burnout: The Role of Student Engagement - Sri Handari Wahyuningsih; Alni Rahmawati; Arif Dwi Saputra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The concept of engagement is widely studied as a necessary positive behavior in the workplace. For this reason, this study aims to examine the engagement and burnout model in higher education by selecting students as study subjects. The determinants taken in this study were the lecturers’ teaching style and the student's achievement motivation. A total of 336 private higher education students in Student City, Indonesia, were used as study subjects. Model testing was done through path analysis. The antecedents of student engagement studied were teaching styles and student achievement motivation. The study results concluded that the teaching style could increase student engagement directly and indirectly through achievement motivation. This finding provides insight into the student engagement and burnout model, built through the lecturers’ teaching style and students’ achievement motivation. In addition, this study implies the significance of higher education attention in improving teaching methods to encourage student motivation and engagement so that learning outcomes are as expected. The two most important limitations, discussed in more detail at the end of the paper, comprised the study's cross-sectional nature and reliance on self-reported questionnaire data. This study implies the importance of higher education paying attention to efforts to increase student engagement and reduce burnout through the achievement motivation and teaching style determinants.